Analysis of the syntactic structures of figure skating narratives - Quintero Ramírez, Sara (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This article characterizes the syntactic structures of spoken narratives of figure skating events. For this, we consider the narratives of four different performances of figure skating with their respective transcription. Based on studies focused on sports discourse, we distinguish the fragments of the spoken narratives in which the journalists intervene to present the event. Subsequently, we identify the structures used in each intervention. At last, we determine the syntactic configuration of the structures used in the corpus in order to distinguish certain syntactic patterns of the structures in the discourse of this sports discipline. With this article we intend to contribute to studies on sports discourse, particularly those focused on syntax of figure skating discourse.